Activities of the EAEU Countries to achieve the Implementation of Sustainable Development Goals - A. V. Toropygin; T. V. Iroshkina (Евразийская интеграция: экономика, право, политика, 2024)
During the period of the global political crisis, there was a forced revision of many international and global initiatives initiated by the UN. Despite the different opinions among states regarding the advisability of continuing the Sustainable Development Goals program, the UN and most countries do not question the need for its continuation.The slowdown of the globalization process, the segmentation of the global space, and the emergence of regional processes to the fore have become an incentive for the development of regional integration structures. To a large extent, of the three hierarchical levels (global, regional, national), the value of the middle level has increased.The article examines the activities of the EAEU to achieve sustainable development goals. It is shown that achieving the SDGs is viewed through the prism of achieving integration priorities reflected in the EAEU Development Strategy-2025.Aim. Describe the activities of the regional integration structure of the EAEU to achieve the SDGs.Tasks. Consider the main monitoring mechanisms for achieving the SDGs in the activities of the EAEU.Methods. To achieve the objectives of the study, descriptive and comparative methods were used.Results. It has been demonstrated that the introduction of SDGs into the regional agenda has a stimulating effect on the development strategy of the EAEU.Conclusions. The global crisis has stimulated closer attention to the regional level of development, where, in economic terms, integration structures play a major role. Achieving the SDGs contributes to economic development, social progress and democracy through achieving sustainable development of member states. In a period of severe confrontation between the world’s majorities and minorities, the SDG concept has shown its relevance as the most general guideline for the development of the world. Throughout the years after the adoption of the development program, international multilateral meetings at various levels, including at the UN level, were not interrupted, discussing the results of achieving the SDGs by the world’s RIOs.